Stability in inverse problem of an elastic plate with a curved middle surface. (16th March 2023) - Fu, Song-Ren; Yao, Peng-Fei
Abstract: We consider stability in an inverse problem of determining three spatially varying functions including the source term and the mass density for a curved plate by the Riemannian geometrical approach. The stability is derived by the Carleman estimates and observability inequalities. Two kinds of boundary conditions are considered: one is the hinged boundary conditions and the other is the clamped boundary conditions. In particular, the case of the Euler–Bernoulli plate is included.